Pengembangan E-Modul Analisis Proses Bisnis Sistem Informasi Untuk Mahasiswa Teknik Informatika - Aniek Suryanti Kusuma; Ketut Agustini; Wawan Sudata (UHN IGB Sugriwa Denpasar, 2023)
Implementation of the learning process at the Indonesian Institute of Business and Technology (INSTIKI), using a Learning Management System called ELSA. All teaching materials contained in ELSA are electronic modules, but these modules are only duplications of printed modules without changing the presentation inside. The presentation of the E-modul cannot accommodate direct knowledge and educational goals cannot be achieved. The purpose of this research is to develop an e-modul of information system business process analysis to support the course of information system analysis and design. The method used in this study is the research and development (R&D) method using the ADDIE approach model stages. This research will be carried out in several stages, namely the first stage of analyzing student needs and analyzing the curriculum. The second stage is designing the e-modul by determining the elements needed in the e-modul. The third stage is the product realization stage according to the design. The fourth stage was implementing the e-modul with Flip book maker and Canva. The fifth stage evaluates the implementation results through small group tests and tests the effectiveness of the product. The result of this research is that the resulting product can increase students' understanding in designing an information system. The quality of the information system business process analysis e-modul stated that this teaching material has good quality and is suitable for use in learning based on validation carried out by material experts with an average value of 0.93 while media experts with an average value of 0.9 and 6 students with an average value of 0.83. Teaching materials in the form of e-moduls are declared valid because they have a very good average.